CFBPSO sebagai Solusi Economic Dispatch pada Sistem Kelistrikan 500 kV Jawa-Bali - Sabhan Kanata (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
The most substantial component of the operating cost of thermal generation is fuel costs. The problem of how to minimize the cost of fuel to determine the combination of the output power of each generating unit with the fulfillment of load constraint systems and limit the ability of each generating unit known as economic dispatch (ED). In this study, the proposed method Modified Improved Particle Swarm Optimization (MIPSO) approach Contriction Factor Based Particle Swarm Optimization (CFBPSO) then this approach is applied in 2 cases the power system in the case of IEEE 30 bus at loading 800 MW and 500 kV power system Jawa-Bali with 12058 MW peak load. The IEEE 30 bus simulation results, the method MIPSO with CFBPSO approach is able to produce the most optimal economic solution than IPSO approach and Quadratic Programming. For the case of 500 kV power system is Jawa-Bali, MIPSO method with this approach is also able to provide the most optimal solution compared with the real system PT. PLN (Persero).